Sistema de informação geográfica e análise espacial : o seu papel na administração pública municipal - Scheidegger, Emerson (2010)
The vast majority of the variables dealt with in the public administration activities have a spatial component, that is, a location in geographic space. This has led to the adoption of tools based on Geographic Information Systems (GIS) in the public sect